Essays on the measurement of leverage and risk of banking institutions - Yong, Vincent Gan Beng (2015)
The crux of this thesis is the development of a new methodology to measure leverage, risk and capital adequacy. The key theme of this thesis is the role of leverage in financial crises and financial stability, especially those that involve the banking sector. Furthermore, we argue that the source of systemic risk lies with the endogenous risk of the banking balance sheet. We discuss the challenges in managing and measuring endogenous and systemic risk. Considering the strong evidence that book values of leverage are key state variables, we suggest new methods to manage and measure systemic risk. We then proceed to propose a novel new methodology for risk measurement that is robust and simple to apply at both the firm and systemic levels. It is further shown how the new risk measure can be applied to measure risk and capital adequacy at the bank level. We propose a new risk measure that combines the capital adequacy and leverage ratio into a single dynamic and consistent risk index that is simple to apply, comparable across all firms and multiple time periods and is risk sensitive. The index is aptly named the Capital Leverage Index or CapLev. It is also further shown how we can apply the methodology in constructing a new systemic risk measure, the Systemic Marginal Leverage Index or SysLev. Finally, we apply autoregressive models and Markov switching to study the effectiveness of the new measure and derive conclusions on the role of commercial banks in the 2008-2009 Global Financial Crisis. We find that SysLev outperforms STLFSI. We also find that aggregate balance sheet changes of the commercial banking sector can exert significant short term effects on the real economy. The predicted relationship is much stronger than the relationship between STLFSI and the real economy.